ФОРМУВАННЯ ГОТОВНОСТІ СТУДЕНТІВ ДО САМОМЕНЕДЖМЕНТУ ЯК АКТУАЛЬНА ПЕДАГОГІЧНА ПРОБЛЕМА (Педагогіка вищої та середньої школи, 2022)
The article is devoted to revealing of objective and subjective factors of forming of social-communicative activity of teenagers personality in process of touristik activit